Improving Digital Literacy to Prevent Hoaxes in the Visually Impaired - Valentino Aris; Syamsu Alam; Muhammad Ashdaq; Muhammad Taufik; Andi Ruslan; Muhammad Jamil (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This Community Service Activity was carried out at the Yapti Makassar Special School (SLB-A Yapti Makassar) by the Digital Business Study Program Service Team, FEB-Makassar State University. Some of the problems faced by partners include a lack of literacy for blind people so that hoaxes spread easily and a lack of independence for blind people in accessing information from various sources. The service method used is the implementation of outreach activities to increase the spirit of digital literacy among the visually impaired so that the spread of hoaxes can be prevented. The activity participants were twelve people with visual disabilities who were currently studying at SLB-A Yapti Makassar. The results achieved from this activity include (1) increased enthusiasm for digital literacy among the visually impaired, (2) increased independence in accessing literacy around them, (3) the ability to distinguish between hoaxes and information and data.